Inhibition of post-transcriptional RNA processing by CDK inhibitors and its implication in anti-viral therapy - Holcakova, Jitka; Muller, Petr; Tomasec, Peter; Hrstka, Roman; Nekulova, Marta; Krystof, Vladimir; Strnad, Miroslav; Wilkinson, Gavin W G; Vojtesek, Borivoj (PloS one, 2014)
Cyclin-dependent kinases (CDKs) are key regulators of the cell cycle and RNA polymerase II mediated transcription. Several pharmacological CDK inhibitors are currently in clinical trials as potential cancer therapeutics and some of them also exhibit antiviral effects. Olomoucine II and roscovitine, purine-based inhibitors of CDKs, were described as effective antiviral agents that inhibit replication of a broad range of wild type human viruses. Olomoucine II and roscovitine show high selectivity for CDK7 and CDK9, with important functions in the regulation of RNA polymerase II transcription. RNA polymerase II is necessary for viral transcription and following replication in cells. We analyzed the effect of inhibition of CDKs by olomoucine II on gene expression from viral promoters and compared its effect to widely-used roscovitine. We found that both roscovitine and olomoucine II blocked the phosphorylation of RNA polymerase II C-terminal domain. However the repression of genes regulated by viral promoters was strongly dependent on gene localization. Both roscovitine and olomoucine II inhibited expression only when the viral promoter was not integrated into chromosomal DNA. In contrast, treatment of cells with genome-integrated viral promoters increased their expression even though there was decreased phosphorylation of the C-terminal domain of RNA polymerase II. To define the mechanism responsible for decreased gene expression after pharmacological CDK inhibitor treatment, the level of mRNA transcription from extrachromosomal DNA was determined. Interestingly, our results showed that inhibition of RNA polymerase II C-terminal domain phosphorylation increased the number of transcribed mRNAs. However, some of these mRNAs were truncated and lacked polyadenylation, which resulted in decreased translation. These results suggest that phosphorylation of RNA polymerase II C-terminal domain is critical for linking transcription and posttrancriptional processing of mRNA expressed from extrachromosomal DNA.
Keywords: Chlorocebus aethiops; Phosphorylation; RNA Polymerase II; Humans; Promoter Regions, Genetic; inhibitory proteinkinas; Roscovitine; RNA Processing, Post-Transcriptional; Cell Cycle; fosforylace; cyklin-dependentní kinasy; Cyclin-Dependent Kinases; roskovitin; ledviny; Kidney; Purines; lidé; posttranskripční úpravy RNA; zvířata; buněčné linie; Cercopithecus aethiops; Protein Kinase Inhibitors; RNA-polymerasa II; Cell Line; DNA virů; puriny; DNA, Viral; Animals; buněčný cyklus; promotorové oblasti (genetika)